Secretory Profile of Metapleural Gland Cells of the Leaf-Cutting Ant Acromyrmex coronatus (Formicidae: Attini) - Vieira, Alexsandro Santana [UNESP]; Bueno, Odair Correa [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Wiley-Blackwell, 2011)
Ants present a pair of metapleural glands located at the posterolateral end of the thorax. Because of its importance in the social organization of ants, the present study was aimed at describing the morphophysiology of this gland in three worker castes of Acromyrmex coronatus, focused on secretory activity using histological and histochemical techniques. Our findings revealed that the secretory and the storage portions of this gland are connected by extracytoplasmic portion of canaliculi that drain the secretion from each secretory cell to the collecting chamber. This secretion contains glycoproteins. In minor workers, the secretion contains higher levels of polysaccharides when compared to that of major workers, supporting the role of the metapleural gland in the maintenance of the fungus garden. The nucleus as well as cytoplasm of secretory cells were strongly positive for RNA indicating that these cells are active in the synthesis of proteins and lipids, compounds found in the final secretion. The variant of the CEC revealed that the secretory activity of the entire gland is synchronous, as all cells exhibit the result. Microsc. Res. Tech. 74:76-83, 2011. (C) 2010 Wiley-Liss, Inc.
Keywords: Acromyrmex coronatus; Attini; metapleural gland; secretory cells